A FEW REPRESENTATIVES OF ASTEROIDAE (ASTERACEAE) SUBFAMILY AND GERANIUM (GERANIACEAE) GENUS IN THE BAIKAL REGION (REVIEW - E. G. Privalova (Фармация и фармакология (Пятигорск), 2021)
The aim of the article was to analyze the state of knowledge of the following plants: Heteropappus altaicus (Willd.) Novopokr., Solidago dahurica L., Leucanthemum vulgare Lam., Tripleurospermum inodorum (L.), Antennaria dioica (L.) Gaertn., Leontopodium conglobatum (Turcz.) Hand.-Mazz. and Geranium eriostemon Fischer., G. pratense L., G. wlassowianum Fisch. ex Link. (Geraniaceae).Materials and methods. To compile the review, the information from the following scientific open and available literature sources placed in scientific libraries of institutions, in electronic databases and search systems, was used: floristic summaries “Flora of Siberia”; “Flora of Central Siberia”; Electronic library of the Siberian branch of the Russian Academy of Sciences; Elibrary; PubMed; Scopus; CyberLeninka, Google Academy; The Plant List, Global Compositae Checklist. The search carried out, was based on the publications for the period of 2009-2020, on the information requests for names of families and subfamilies, names of plant species, biologically active compounds in English, Latin and Russian.Results. A comparative analysis of morphological characters, common species names and the synonyms for the listed species, has been carried out. The studied objects are characterized by the presence of polyphenolic compounds and substances of a triterpene structure, in particular, flavonoids, hydroxycinnamic acids, tannides. In addition, the representatives of the Asteroideae subfamily (Asteraceae) show the accumulation of essential oils, and the representatives of the Geranium genus (geranium) show the accumulation of anthocyanins. The spectrum of the pharmacological activity includes anti-inflammatory, choleretic, antimicrobial, antispasmodic and other types of effects.Conclusion. The presented review makes it possible to arrive at the conclusion about a certain knowledge level of the regional representatives of the Asteroideae subfamily and the Geranium genus. This determines the prospects of these plant objects for further pharmacognostic and pharmacological research and the creation of drugs on their basis – the sources of polyphenolic compounds.